2021
DOI: 10.1080/02643944.2021.1938644
|View full text |Cite
|
Sign up to set email alerts
|

The mental health and emotional needs of secondary age students in the United Kingdom

Abstract: There is a growing policy focus on children and young people's mental health. The United Kingdom (UK) government has positioned schools as being well-placed to identify children and young people's mental health needs and to provide appropriate intervention. At the same time, school staff report a lack of skills, knowledge and systems to support the early identification of mental health needs in order to inform appropriate intervention. The aim of this study was to explore the mental health and emotional needs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…This proposes that for an individual to be emotionally healthy, the following emotional needs should be met: security, receiving and giving attention, control, feeling part of the wider community, privacy, emotional connection to others, sense of status, sense of competence, and meaning (Human Givens Institute, 2006). A large‐scale study among UK secondary school students indicated that where these needs went unmet, students were more likely to report depressive symptoms (Waite et al, forthcoming). Attwood and Atkinson (2020) proposed that the approach could provide a template for offering support to students with learning difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…This proposes that for an individual to be emotionally healthy, the following emotional needs should be met: security, receiving and giving attention, control, feeling part of the wider community, privacy, emotional connection to others, sense of status, sense of competence, and meaning (Human Givens Institute, 2006). A large‐scale study among UK secondary school students indicated that where these needs went unmet, students were more likely to report depressive symptoms (Waite et al, forthcoming). Attwood and Atkinson (2020) proposed that the approach could provide a template for offering support to students with learning difficulties.…”
Section: Introductionmentioning
confidence: 99%